Ocorrência e identificação molecular de espécies do gênero Mycobacterium e marcadores de virulência em linhagens de Rhodococcus equi isoladas de linfonodos e das fezes de suínos de abatedeouro - Lara, Gustavo Henrique Batista [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The infectious lymphadenitis represents one of the most important diseases in pigs worldwide caused by bacterium, usually diagnosed on the slaughterhouses.The disease leads to economic losses due to total or partial condemnation of carcasses, as well as public health concern due to the zoonotic potential of microorganisms. The present study investigated the occurrence and the main species of the genus Mycobacterium as well as virulence markers of plasmid in Rhodococcus equi (R. equi) strains isolated from lymph nodes and feces from pigs of slaughterhouses in the state of São Paulo, with and without lymphadenitis. Were sampled 150 lymph nodes (50 mesenteric, 50 mediastinal and 50 submandibular) with lesions, 150 lymph nodes (50 mesenteric, 50 mediastinal and 50 submandibular) without visible lesions, and 150 feces from pigs of slaughterhouses of state of São Paulo, Brazil. The lymph nodes samples and feces were subjected to microbiological culture simultaneously indefibrinated bovine blood agar (5%), selective media of CAZ-NB, TCP, TVP for R. equi, and Stonebrink-Lesslie, and Lowenstein-Jensen for mycobacteria . The suggestive colonies of R. equi and positive to CAMP test were sent to Japan for evaluation of plasmid profile (VapA or VapB). The suggestive of Mycobacterium sp. were subjected to polymerase chain reaction (PCR) – based species identification using restriction enzyme pattern analysis (PRA). Among lymph nodes of pigs with lesions, 48 (32.0%) Mycobacterium spp. and 6 (4.0%) R. equi strains were identified. In the lymph nodes of pigs without lesions were identified 11 (7.3%) Mycobacterium spp. and none R. equi strain. From the fecal samples, 40 (26.6%) R. equi and 2 (1.3%) Mycobacterium spp. isolates were identified. From 48 Mycobcterium isolates from pigs with lesions, 37 (77.0%) were identified by PRA as M. avium type 1, and 11 (23.0%) M. avium type 2. Among limph nodes with lesions wer ...

A linfadenite infecciosa em suínos representa uma das afecções mais preocupantes na criação de suínos em todo mundo, causada por patógenos de origem bacteriana, geralmente diagnosticada na linha de abate. Acarreta prejuízos econômicos com a condenação total ou parcial das carcaças, bem como reflexos em saúde pública, devido ao potencial zoonótico dos agentes causais. O presente estudo investigou a ocorrência e as principais espécies do gênero Mycobacterium, assim como marcadores de virulência plasmidial em linhagens de Rhodococcus equi (R. equi) isoladas de linfonodos e das fezes de suínos de abatedouros do interior do estado de São Paulo, com e sem linfadenite. Foram examinados 150 linfonodos (50 mesentéricos, 50 mediastínicos e 50 submandibulares) com lesões, 150linfonodos (50 mesentéricos, 50 mediastínicos e 50 submandibulares) sem lesões aparentes e 150 fezes de suínos, provenientes de animais destinados ao abate, em dois frigoríficos do interior do estado de São Paulo. As amostras de linfonodos e fezes foram submetidas ao cultivo microbiológico simultaneamente nos meios de ágar acrescido de sangue bovino (5%) desfibrinado, e meios seletivos de CAZ-NB, TCP e TVP para R. equi, e Stonebrink–Lesslie e Lowenstein-Jensen para micobactérias. As colônias sugestivas de R. equi e positivas no teste de CAMP, foram enviadas ao Japão para detecção de linhagens VapA ou VapB, associadas a virulência. As linhagens sugestivas no cultivo microbiano para o gênero Mycobacterium foram submetidas a caracterização de espécies por PCR pela técnica de PRA. Foram identificados nos linfonodos de suínos com lesões 48 (32,0%) linhagens de Mycobacterium spp.e 6 (4,0%) Rhodococcus equi. Nos linfonodos de suínos sem lesões foram identificados 11 (7,3%) isolados de Mycobacterium spp.e nenhuma linhagem de R. equi. Nas fezes foram identificadas 40 (26,6%) linhagens de Rhodococcus equi e ...
Keywords: Suino - Doenças; Rhodococcus equi; Doenças micobacterianas; Virulencia (Microbiologia); Linfadenite caseosa